METHODOLOGY FOR PREPARING FUTURE LOGIC THERAPISTS TO WORK ON ALALIYA SPEECH DEFECTS (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the characteristics of children with alalic speech defects and the speech therapy work system carried out with them and the methodology of preparing future speech therapists to work on alalic speech defects are highlighted.